Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Legal Tender Band: Bob Fishman and John B. Smith on guitar, Lorraine Bolen on tambourine, Dave Maybary on saxophone, Nano Tanaloa on guitar, Ken Fransen on percussion playing Star Wars theme music 5080 E. Kings Canyon Road, Fresno